Effect of nanofillers in jute/carbon hybrid reinforced polylactic acid composite - Sairy, Nur Aqilah (2021)
The presence of fibres and fillers in a composite can be efficiently arrest crack either at the macro or micro levels. In this work, woven jute and carbon fibres were arranged alternately in polylactic acid (PLA) composite. Graphene or nanoclay was embedded into the PLA matrix to make a polymer nanocomposite. Fibre-reinforced polymer composites were prepared by varying the concentration (1, 3, 5wt%) of graphene or nanoclay in the PLA matrix. The alternate woven jute and carbon fibres aere then bound with the PLA nanocomposite. The influence of graphene or nanoclay concentration and the presence of woven fibres in the composite were quantified by flexural analysis. Flexural strength and flexural modulus were found to increase at 3wt% of nanofiller concentration for graphene/jute/PLA and nanoclay/jute/PLA nanocomposites with the increments up to 37% and 31%, respectively. Lowvelocity impact revealed that PLA/TJ/C/G1, PLA/TJ/C/G3, and PLA/TJ/C/G1 have the highest force value for 7J, 10J, and 13J, respectively. These three optimum values for each energy indicate that the closed curve results from the striker’s inability to penetrate the specimen. Thus, it was assumed that the lower loading of graphene could withstand the impact energy of 7J, 10J, and 13J. FTIR was used to determine the interaction between PLA and nanofillers. Morphology observation by Scanning Electron Microscopy (SEM) was done to investigate the fractured surface of the hybrid jute/carbon fibres reinforced PLA nanocomposite.